IDENTIFIKASI SEKTOR UNGGULAN: MENINGKATKAN KEMAJUAN KOTA PADANGSIDIMPUAN - Masta Juwita Gurning (JURNAL EKOMBIS, 2021)
This study aims to determine the most contributing sector to Padangsidimpuan’s regional economy. This research uses secondary data in the form of time series from Gross Regional Domestic Product (GRDP) of Padangsidimpuan and North Sumatera province during the period 2015-2019. The analytical tools used in this research are: 1). Location Quotient (LQ) which is used to determine the base sector and non bases in the economy of Padangsidimpuan. 2). Shift Share Analysis is used to determine changes and shifts in economic structure of Padangsidimpuan. Results of analysis per sector based on both analytical tools show that the dominant sector in Padangsidimpuan which belong to criteria of base and competitive sectosr is the education services sector.